Barnfattigdom, en studie om barnfattigdom ur socialarbetares perspektiv - Adibi,Kamelia (2024)
This study investigates, from the social workers' point of view, how child poverty affects the normal development of children and young people, what strategies vulnerable children and young people use to deal with economic hardship in their everyday lives, and how the child's perspective and child poverty are understood and considered in the social work with children, young people, and families. A qualitative research method is used to collect data through seven semi-structured interviews with social workers who work with children, young people, and families in different organisations. The study results show that child poverty is understood based on the family's financial conditions. In addition, vulnerable children and young people use different strategies, such as participating in free activities, watching TV, playing computer games, etc., to deal with economic hardship in their everyday lives. The results demonstrate that strong and positive ties between children and people in their surrounding environment (microsystem), such as parents and friends, can lead to better resilience against the family's economic hardship. The results also show that the child's perspective is taken into account largely based on the parents' perspective in social work, when parents seek financial assistance.
Keywords: child poverty; children's development; children's strategies; children's interactions; economic hardship; children's perspective; social identity; stigma; children's social life